Financial Performance Assessment using Economic Value Added (EVA) and Market Value Added (MVA) in Property Companies in Indonesia - Ni’matus Sholikhah; Fauzan Nenza Z; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2024)
.These reports depict a clear picture of a company's assets, liabilities, income, and expenses, offering a profound understanding of its financial performance and stability. This research aims to conduct a Financial Performance Assessment using Economic Value Added (EVA) and Market Value Added (MVA) with a Time Series Approach on Property Companies in Indonesia. This is a descriptive study, employing purposive sampling techniques and utilizing secondary data in the form of annual financial reports over a period of 5 years from 2018 to 2022. The study focuses on five major Real Estate sector companies listed on the Indonesia Stock Exchange: Armadian Karyatama, Bhakti Agung Properindo, Bumi Serpong Damai, Capri Nusa Satu Property. After calculating the variables for each consecutive year, the average assessment of Economic Value Added (EVA) indicates positive results. This suggests that the overall condition of the Property Industry in Indonesia is considered GOOD. However, the Market Value Added (MVA) for the Property Industry from 2018 to 2022 shows negative results. This indicates that the overall condition of the Property Industry in Indonesia is considered NOT GOOD.